Antioxidant and Antidiabetic activities of Alangium salvifolium and Bombax ceiba - Zahan, Ronok; Nahar, Laizuman; Haque, Mahmuda; Nesa, Mst Luthfun; Alam, Zahangir (Dhaka University Journal of Pharmaceutical Sciences, 2014)
In the present study, a methanol extract of flower of Alangium salvifolium (AS) and bark of Bombax ceiba (BC) were evaluated for its antioxidant and antidiabetic activities. Both methanol extracts exhibited DPPH free radical scavenging activity and reducing power activity in dose dependent manner. Continuous administration for of methanol extracts of AS for seven days significantly decreased blood glucose level than BC in alloxan induced diabetic rats at a dose of 200 mg/kg body weight. The IC50 value of AS and BC were 17.3 ?g/ml and 32.1 ?g/ml, respectively. Both extract showed significant decrease of blood sugar after glucose loading points (30, 60 and 120 min). In addition, flower of AS possesses high phenol content than the bark of BC (152.73±13.60 vs 74.38±7.42 mg/g of gallic acid). This is the first report of antioxidant and reducing power evaluation and quantitative analysis of phenol content for this two plant materials. This finding suggest that the potential antioxidant activity and antidiabetic effect of flowers of AS could be due to the presence of phenolic compounds. Dhaka Univ. J. Pharm. Sci. 12(2): 159-163, 2013 (December) DOI: http://dx.doi.org/10.3329/dujps.v12i2.17617